'A brutal blow against the democratic normality': unlearning the epistemology of the political. (2nd November 2017) - Jose, Jim
ABSTRACT: The objective of this paper is to rethink our understanding of 'the political' through an examination of two novels by José Saramago, Blindness and Seeing . Both novels tackle directly a central, if not the central, signature metaphor of Western political thought, namely that of 'seeing the light'. This metaphor takes many forms and recurs throughout the tradition of Western political philosophy as a source, legitimiser, and validator of knowing, and perhaps even a guarantor of knowledge. In particular, this metaphor has served to make knowable whatever it is that is signified by 'the political'. By extension, it also means that whatever might be outside of this epistemological frame is rendered unknowable, if not unthinkable. Both of Saramago's novels provide a fruitful means to recalibrate how we might know 'the political'. The novels call into question the epistemic signatures that frame our commonly accepted understandings of 'the political' and in so doing provoke us further to question how we might move towards unlearning the epistemology of the political.